Effects of Nitrogen Application on Soluble Sugar and Starch Accumulation During Sweet Potato Storage Root Formation - Hong Tham Dong; Yujuan Li; Philip Brown; Delwar Akbar; Cheng-Yuan Xu (Horticulturae, 2025)
Nitrogen is an essential element for plant growth, and both insufficient and excessive use of nitrogen have been shown to negatively affect sweet potato production. Nitrogen supply can affect carbon metabolism in plant storage organs; however, limited studies have examined its effects on the accumulation of non-structural carbohydrates (soluble sugar and starch) during the formation of sweet potato storage roots. Two pot trials were conducted to evaluate the effects of different nitrogen application levels and timings on the accumulation of non-structural carbohydrates during the formation of sweet potato storage roots. In the first experiment, plants were supplied with 0, 50, 100, or 200 mg/L of nitrogen. In the second experiment, the optimum nitrogen rate (100 mg/L) for storage root formation from the previous experiment was applied at five different times: nil N supply and nitrogen applied at planting or 3, 7, or 14 days after planting. A significant highest starch accumulation in roots during the first 35 days after transplanting was recorded in the 100 mg/L treatment. However, sweet potato required more nitrogen after storage root formation, as indicated by higher non-structural carbohydrate accumulation in roots (1905 mg/plant) in the 200 mg/L treatment at 49 days after planting. Earlier nitrogen applications promoted soluble sugar and starch accumulation in plants during storage root formation, with up to 5697 mg of non-structural carbohydrate accumulated in a plant. The study provided agronomic indicators that moderate nitrogen should be available in soil before or on planting day.